Cultivating Islamic Digital Ethics: Implementing Responsible Gadget Use Education among Students - Najwa Abida Alaziza; Suripto Suripto; Siti Nur Hidayatul Hasanah (Al-Ridha: Jurnal Pengabdian kepada Masyarakat, 2026)
The development of information and communication technology has brought significant implications for education, particularly in students’ patterns of gadget use. Although gadgets have become an integral part of students’ daily lives, their use is often dominated by entertainment rather than learning and worship, potentially creating challenges for students’ moral and spiritual development. This community service activity was conducted at SMPN 1 Ngantru, Tulungagung Regency, involving 993 students from Grades VII, VIII, and IX. The activity aimed to strengthen students’ understanding of Islamic manners in gadget use and encourage them to utilize digital devices wisely, productively, and in ways that support worship. The activity employed interactive lectures, discussions, ice-breaking activities, and simple evaluations. The effectiveness of the activity was evaluated through students’ responses to questions about Islamic manners in gadget use, their participation and enthusiasm during discussions and activities, and their ability to identify appropriate and inappropriate patterns of gadget use in relation to learning, entertainment, and worship. The results showed that students demonstrated better understanding of appropriate gadget use, active participation in discussions, and greater awareness of the importance of limiting entertainment-oriented use and maintaining discipline in worship. These findings indicate that integrating Islamic literacy with interactive activities can provide a practical approach to strengthening students’ digital ethics and character in the context of contemporary technology use. The activity highlights the importance of incorporating Islamic digital ethics into character education to guide students toward responsible, productive, and spiritually meaningful gadget use.